2019
DOI: 10.1186/s40478-019-0768-5
|View full text |Cite|
|
Sign up to set email alerts
|

Retinal pathology in experimental optic neuritis is characterized by retrograde degeneration and gliosis

Abstract: The exact mechanisms and temporal sequence of neurodegeneration in multiple sclerosis are still unresolved. The visual pathway including its unmyelinated retinal axons, can serve as a prototypic model of neurodegeneration in experimental optic neuritis. We conducted a longitudinal study combining retinal imaging through optical coherence tomography (OCT) with immunohistochemical analyses of retinal and optic nerve tissue at various time points in experimental autoimmune encephalomyelitis (EAE). Inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 82 publications
(95 reference statements)
5
62
0
Order By: Relevance
“…The power analysis using our previously published results with alpha-lipoic acid [8] revealed that protective effects of 20% on the retinal structure could be detected with 14 animals per group, which is in line with other studies using similar methodology [9, 39, 40]. Interestingly, OKR analysis of visual function and RGC counting in retinal wholemounts showed less variance resulting in numbers as low as 3 animals per group in the power analysis to detect 15% protection of visual function and 25% protection of RGCs.…”
Section: Discussionsupporting
confidence: 87%
“…The power analysis using our previously published results with alpha-lipoic acid [8] revealed that protective effects of 20% on the retinal structure could be detected with 14 animals per group, which is in line with other studies using similar methodology [9, 39, 40]. Interestingly, OKR analysis of visual function and RGC counting in retinal wholemounts showed less variance resulting in numbers as low as 3 animals per group in the power analysis to detect 15% protection of visual function and 25% protection of RGCs.…”
Section: Discussionsupporting
confidence: 87%
“…Optic neuritis (ON) is a major source of disability in patients with inflammatory central nervous system diseases such as multiple sclerosis, and trials on optic neuritis are increasingly being applied to evaluate neuroprotective strategies [ 1 ]. Myelin oligodendrocyte glycoprotein-induced experimental autoimmune encephalomyelitis is reportedly associated with strong optic neuritis (EAEON) resulting in demyelination and axonal damage of the optic nerve and in the following degeneration of the inner retinal layers: retinal nerve fiber layer (axons), ganglion cell layer (neurons), and inner plexiform layer (dendritic arbor) [ 2 6 ]. Studies on preclinical models of experimental autoimmune encephalomyelitis optic neuritis (EAEON) are ideally suited to translationally evaluate the promise of clinical ON trials especially since more and more in vivo clinical readouts are being adapted to the preclinical setting [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…202 More than 70% of MS patients suffer vision loss as a secondary effect of optic neuritis disease progression. 160,203,204 In recent studies, Klotho was shown to accelerate remyelination in a cuprizone-mediated demyelination mouse model. 9,28 This important finding is refocusing attention on Klotho's role in neurodegeneration and research efforts are increasingly directed toward the develop-ment of MS treatments that promote remyelination and/or stimulate myelin repair.…”
Section: Introductionmentioning
confidence: 99%